Loose nominals - Raghotham, Sreekar (Proceedings of the Amsterdam Colloquium, 2024)
Proxy readings of nominals are a type of loose talk. They show the same empirical signature as other instances of loose talk. I model this behaviour by treating proxy readings as resulting from underspecification of individuals. This view helps better understand the behaviour of intensive reflexives and indexiphors.